Association between malnutrition and contrast-associated acute kidney injury in congestive heart failure patients following coronary angiography - Ying, Ming; Yang, Junqing; Huang, Zhidong; Ling, Yihang; Wang, Bo; Huang, Haozhang; Li, Qiang; Liu, Jin; Liu, Yong; Chen, Zhujun (Frontiers in Nutrition, 2022)
Background: Previous studies have shown that malnutrition is very common in patients with congestive heart failure (CHF) and is closely related to the occurrence of acute kidney injury. However, the relationship between malnutrition and contrast-associated acute kidney injury (CA-AKI) is unclear. Method: We obtained data from 842 patients who were diagnosed with CHF following coronary angiography (CAG) and had follow-up information from January 2013 to February 2016. The patients were divided into 3 groups (quartile 1: normal; quartile 2: mild; and quartile 3: moderate or severe malnutrition). The main endpoint was CA-AKI. Univariate and multivariate logistic regression analyses were performed. Results: During a median follow-up of 5.25 years, 556 (60.0%) patients suffered from malnutrition. A total of 49 (5.82%) patients developed CA-AKI. Additionally, 5 (1.75%), 26 (6.27%) and 18 (12.77%) events were documented in patients with normal, mild and moderate or severe malnutrition, respectively (p<0.01). In multivariable-adjusted models, patients with malnutrition showed a significantly higher incidence of CA-AKI than those in the normal group. Conclusion: Malnutrition is an independent risk factor for CA-AKI in CHF patients following CAG and is associated with long-term mortality.